Wisdom and Ethics: The Contribution of Sapiential Ethics for Old Testament Ethics - Baumann, G. (Verbum et ecclesia, 2009)
Old Testament sapiential literature is often described as “ethical literature“, however, when concepts on Old Testament ethics are formulated, this literature is often overlooked. Furthermore, there are almost no monographs on the ethics of Old Testament wisdom. Could this perhaps be due to not only the claim that Old Testament wisdom thinking lacks divine revelation or reference to other Old Testament traditions (cf Nel 2002:435), but also to the opinion that there are no “ethics“, but only “ethos“ in this kind of literature? This article tries to show that “ethics” by definition can be found in Old Testament wisdom literature. Two recent German articles are introduced to the reader: Kaiser (1997) and Zimmermann (2002) reflect on the implicit and explicit ethics of Old Testament wisdom. These articles and other observations underscore the fact that the sapiential literature of the Old Testament contribute significantly to Old Testament ethics - and therein continues the efforts of authors like Nel (2002).